Enhancing Tourism through Social Context Marketing Model (SCXM) - Zainul Wasik; C. Candraningrat2 Candraningrat; Wulan Purnamasari (PT. Mawadaku Sukses Solusindo, 2025)
As people are able to combine data from several sources on their mobile devices, personalise their profiles via applications and social media, and engage dynamically with their environment, context-based marketing is becoming more and more common. There is a growing need for more contextually relevant data due to the abundance of information available online. Modern Information and Communication Technologies (ICTs) are becoming increasingly important to the tourism industry because they provide tools to better target the context in which their users work. Context-aware marketing makes use of technology that dynamically identify consumers' physical surroundings. This essay combines the ideas of personalisation, social media, context-based marketing, and mobile devices, proposing the Social Context Marketing Model (SCXM) as a novel approach to enhance value for everybody involved in the tourist sector. With the introduction of a new paradigm for travel and tourism, SCXM enables businesses and tourist locations to transform their offers and dynamically co-create goods and services with customers. The tourist industry's new prospects and problems are examined using a notional SCXM model.